Vitamin C inclusion levels in chicken and quail egg yolk tri- sodium citrate extenders on motility and viabilty of friesian x bunaji bull semen over storage period - Achi, N.P.; Achi, J.N. (Nigerian Journal of Animal Science, 2023)
An experiment was conducted to evaluate the effect of vitamin c inclusion levels in chicken and quail egg yolk tri-sodium citrate extender on Friesian x Bunaji bull semen characteristics. Semen was collected weekly with the aid of an artificial vagina for five weeks. Three (3) Friesian × Bunaji bulls between 2-3 years of age were used for the study. Vitamin C was included at 0, 3 and 6mg/ml in chicken and quail egg yolk extenders. Samples were analysed for initial spermatozoa characteristics, which include colour, volume, live and dead sperm cells, motility, pH, concentration and morphology. Extended semen was then stored for 0, 24, 48 and 72 hours, respectively at a temperature of about 5oC. The result of this experiment shows that the inclusion levels of Vitamin C on chicken and quail egg yolk extender had significant effect (P<0.05) on motility and viability of Friesian x Bunaji bull spermatozoa. After 72 hours there was significant difference (P<0.05) on motile and viable sperm cells in the quail and chicken egg yolk extenders with higher inclusion level of Vitamin C compared to their control. It can be concluded that inclusion of Vitamin C in chicken and quail egg yolk tri-sodium citrate extenders aid in maintaining chilled semen motility and viability up to 72 hours of storage.